On the Art of Healing: Simone Leigh’s The Waiting Room - Krasny, Elke (Socialmedicinsk tidskrift, 2019)
The following essay centers on artist Simone Leigh’s work The Waiting Room which took place at the New Museum in New York in 2016. The analytical reflections presented here connect the description of the social and aesthetic strategies of The Waiting Room, a key example of health activism and black feminist practice in contemporary art making, to the broader context of the politics of health, the crisis of social reproduction under neoliberalism, and the gendered and racialized body.